Fair Resource Allocation Among Children and Adolescents: The Role of Group and Developmental Processes. (14th November 2016) - Rutland, Adam; Killen, Melanie
Abstract: The fair exchange of resources provides a basis for developing morality, yet research has rarely examined the role of group processes that are central to children's world. In this article, we describe a new perspective as well as research demonstrating that group processes play a key role in the fair allocation of resources among children and adolescents. We contend that when children allocate resources, group processes and moral judgments are relevant, a developmental shift occurs in children's ability to coordinate moral and group concerns, and group processes contribute to intergroup bias regarding allocations but also to efforts to consider the status of disadvantaged groups. Our perspective informs efforts to reduce prejudice as well as increase fairness and equality in situations in which group processes are relevant for allocating resources fairly.